The Effects of Resource Rent, Human Capital and Government Effectiveness on Government Health Expenditure in Organization of the Petroleum Exporting Countries - Nikzadian, Ali; Agheli, Lotfali; Assari Arani, Abbas; Sadeghi, Hossein (International Journal of Energy Economics and Policy, 2019)
The low economic growth and lack of qualified institutions have led to a lower level of health in the resource-rich developing countries. This paper explores the effects of resource rent, human capital and government effectiveness on government health expenditure in Organization of the Petroleum Exporting Countries (OPEC). It uses Panel Fully Modified Least Squares (Panel-FMOLS) method in Eviews software over the period 2002 – 2015. Findings imply that the resource rent, human development index and government effectiveness influence directly the government expenditure on health, when the interactions between explanatory variables are ignored. However, the sign and magnitude of coefficients are changed, when interaction terms are included in regression models. The oil rents affect the healthcare sector in OPEC. Accordingly, the abundance of oil resources is not bad per se. Thus, the key determinant in the transformation of rents from oil resources into disaster or blessing is the government effectiveness across oil exporting countries. Keywords: Health, Resource rent, Panel-FMOLS JEL Classifications: C52, I15, P48 DOI: https://doi.org/10.32479/ijeep.7575